2007
DOI: 10.1111/j.1467-9450.2007.00578.x
|View full text |Cite
|
Sign up to set email alerts
|

Empathy, guilt, and gender: A comparison of two measures of guilt

Abstract: The relations of empathy with two measures of guilt were examined in a sample of 13- to 16-year-olds (N= 113). Empathy was measured using Davis's IRI and guilt by Tangney's TOSCA and Hoffman's semi-projective story completion method that includes two different scenarios, guilt over cheating and guilt over inaction. Empathy correlated more strongly with both measures of guilt than the two measures correlated with each other. For boys, cognitive perspective-taking was a stronger predictor for guilt than for girl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 30 publications
(43 reference statements)
4
17
1
1
Order By: Relevance
“…Consistent with previous research, girls had higher mean scores on both affective and cognitive empathy compared to boys, but the magnitude of the difference was greater for affective empathy [21]. In a separate but related body of empathy research, researchers found that moral judgment of boys was more directly based on perspective-taking, a cognitive aspect of empathy, compared to moral judgment of girls [25]. Even though it could be argued that low affective empathy is the key variable contributing to offline bullying behavior [12], cyberbullying has similarities with indirect bullying which has links with cognitive empathy.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Consistent with previous research, girls had higher mean scores on both affective and cognitive empathy compared to boys, but the magnitude of the difference was greater for affective empathy [21]. In a separate but related body of empathy research, researchers found that moral judgment of boys was more directly based on perspective-taking, a cognitive aspect of empathy, compared to moral judgment of girls [25]. Even though it could be argued that low affective empathy is the key variable contributing to offline bullying behavior [12], cyberbullying has similarities with indirect bullying which has links with cognitive empathy.…”
Section: Discussionsupporting
confidence: 77%
“…Perspective-taking is a central part of Kohlberg's [24] cognitive-developmental theory of moral judgment. Interestingly, Silfver and Helkama [25] found that for adolescent boys, cognitive perspective taking was a stronger predictor of guilt than for girls. This finding was in line with previous research showing that moral judgment of boys was more directly based on cognition compared to girls [26].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Like empathy, sympathy also has been found to be positively associated with prosocial behavior (for reviews, see Eisenberg et al, 2006Eisenberg et al, , 2010Hoffman, 2000) and negatively associated with aggression (Carlo et al, 2010;MacEvoy & Leff, 2012). Furthermore, previous research with children and adolescents has shown that guilt is negatively related to aggression (Roos, Salmivalli, & Hodges, 2011), bullying (Menesini et al, 2003;Perren, Gutzwiller-Helfenfinger, Malti, & Hymel, 2012), and antisocial behavior (Lotze, Ravindran, & Myers, 2010) and positively associated with empathy (Hoffman, 2000;Silfver & Helkama, 2007) and prosocial behavior (Olthof, 2012). Hence, it is reasonable to assume that moral emotions as an index of empathy, sympathy, and guilt have an impact on students' behavior in bullying situations.…”
Section: Moral Emotionsmentioning
confidence: 99%
“…Empathetic people, in contrast, tend to feel for the victim and suffer more readily if they see that others are hurt (Hoffmann, 2000). Consequently, empathetic people are more prone to feeling guilty (Hoffmann, 1998(Hoffmann, , 2000Silfver & Helkama, 2007;Tangney et al, 2007), especially if they are involved in interpersonal violence (Thompson & Hoffman, 1980). Likewise, research in the domain of television and movies suggests that more empathetic users feel more sympathetic towards victims of violence (e.g., Raney, 2002), and that users RUNNING HEAD: Virtual Violence and Guilt 9 dislike violence directed towards characters they feel empathetic with (Zillmann, 1991).…”
Section: User-factor Influencing Guilt Responses: Trait Empathymentioning
confidence: 99%